Quality Management in the Professional Development of High School Teachers at Methodist Banda Aceh: A Literature Review - Rahmat Hidayat Rahmat (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This literature review explores the significance of quality management in the professional development of high school teachers at Methodist Banda Aceh. As educational institutions increasingly recognize the critical role that teacher effectiveness plays in student achievement, the implementation of quality management principles becomes paramount. This review synthesizes existing research on various quality management frameworks, such as Total Quality Management (TQM), Continuous Improvement Processes, and Six Sigma, and evaluates their applicability in the context of teacher professional development. The study emphasizes three main areas: enhancing pedagogical skills, fostering teacher motivation, and optimizing educational outcomes. By analyzing case studies and evidence from similar institutions, we identify best practices that can be adapted to the unique context of Methodist Banda Aceh. The findings reveal that structured quality management initiatives not only promote skill enhancement through targeted training and workshops but also create a culture of accountability and continuous learning among educators. Furthermore, the review discusses the impact of mentorship programs and peer assessments as integral components of a comprehensive quality management strategy aimed at improving teaching effectiveness. Ultimately, this literature review underscores the necessity for a systematic approach to professional development that incorporates quality management principles to ensure sustained improvement and excellence in education. It calls for further research on the long-term outcomes of these practices in enhancing both teacher satisfaction and student performance, contributing to the broader discourse on educational quality in Indonesia.